Health Counseling on Drugs at SMP Negeri 3 Tanjung Jabung Timur - Yersi Ahzani; Meri Anggryni; Minnatun Khasa; Desak Gede Yenni Apriani; Desak Made Firsia Sastra Putri (Jurnal Pengabdian Masyarakat DEDIKASI, 2025)
Introduction: Drug abuse is a growing public health problem, including among school-aged adolescents. National data shows an increasing prevalence in the 15–24 age group, making schools a strategic environment for preventive interventions. Junior high school adolescents are highly vulnerable due to developmental factors, peer pressure, and a lack of knowledge about the risks of drugs. This community service activity was carried out to improve adolescent health literacy and develop preventive attitudes towards drug abuse. Methods: The activity was carried out through face-to-face counseling for 55 students in grades VIII and IX at SMP Negeri 3 Tanjung Jabung Timur. Education used presentation media, interactive discussions, and question and answer sessions. Evaluation was carried out through direct observation of student engagement during the session. Results: The activity ran smoothly and received high enthusiasm from participants. Students were able to answer questions more accurately after the counseling, demonstrating an increased understanding of the types, dangers, and prevention efforts of drug abuse. The discussion was active and showed a change in awareness of the importance of protecting themselves from the negative effects of drugs. Overall, this counseling was effective in improving health literacy and preventive attitudes among adolescents. Conclusion: School-based drug counseling has been shown to improve students' knowledge and attitudes regarding drug abuse prevention. Educational interventions like this need to be carried out continuously with school support to create a drug-free educational environment. Keywords: drugs, health education, adolescents, schools, prevention.